Does farm mechanization improve farm performance and ensure food availability at household level? Empirical evidence from Pakistan - Yasar, Hassan; Raza, Muhammad Haseeb; Faisal, Muhammad; Nadeem, Nasir; Khan, Nawab; Kassem, Hazem S.; Elhindi, Khalid M.; Mahmood, Sammina (Frontiers in Sustainable Food Systems, 2024)
Agriculture has a significant role in the well-being of the rural households of the developing countries. Still, its productivity is very low in these countries due to low use of mechanization at farm level. Also, extreme climate events and labor shortage at required intervals have made decisive pitch for promotion and adoption of farm mechanization for ensuring sustainable farm performance and food security in developing countries. However, limited empirical evidence is available from Pakistan, about adoption of farm mechanization and its impact on the farm performance and food availability. Therefore, primary data was collected from 384 farmers from cotton-wheat cropping system of Punjab, Pakistan by using multi-stage sampling procedure. The endogenous switching regression (ESR) model was employed to estimate the determinants of farm mechanization adoption and their associated impacts on farmers' livelihood, measured by farm performance and food availability. The findings indicate that the adoption of full mechanization across all farming operations enhances overall farm performance and improves food availability. Additionally, full mechanization leads to a substantial increase in farm performance by up to 55% and boosts food availability by approximately 125%. Our study demonstrates that the adoption of farm mechanization is strongly influenced by factors such as education, household size, landholding, off-farm employment, access to credit, and extension services.